2010
DOI: 10.1007/s10709-010-9503-7
|View full text |Cite
|
Sign up to set email alerts
|

The transformer gene of Ceratitis capitata: a paradigm for a conserved epigenetic master regulator of sex determination in insects

Abstract: The transformer gene in Ceratitis capitata (Cctra(ep)) is the founding member of a family of related SR genes that appear to act as the master epigenetic switch in sex determination in insects. A functional protein seems to be produced only in individuals with a female XX karyotype where it is required to maintain the productive mode of expression through a positive feedback loop and to direct female development by instructing the downstream target genes accordingly. When zygotic activation of this loop is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 95 publications
1
48
0
Order By: Relevance
“…Moreover, prevention of maternal Nvtra mRNA did not only lead to disrupted splicing of zygotic Nvdsx pre-mRNA, but also to a disruption of Nvtra pre-mRNA splicing itself. This indicates that Nvtra female-specific splicing also establishes an autoregulatory memory loop, as has been found in several other insect species [Pane et al, 2002;Ruiz et al, 2007;Concha and Scott, 2009;Gempe et al, 2009;Salvemini et al, 2009;Hediger et al, 2010;Saccone et al, 2011]. As blocking maternal provision of female-specific Nvtra mRNA led to a complete sex-reversal of diploid offspring, surprisingly, the mother provides feminizing in addition to masculinizing information to the zygote.…”
Section: Megisd Revisitedsupporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, prevention of maternal Nvtra mRNA did not only lead to disrupted splicing of zygotic Nvdsx pre-mRNA, but also to a disruption of Nvtra pre-mRNA splicing itself. This indicates that Nvtra female-specific splicing also establishes an autoregulatory memory loop, as has been found in several other insect species [Pane et al, 2002;Ruiz et al, 2007;Concha and Scott, 2009;Gempe et al, 2009;Salvemini et al, 2009;Hediger et al, 2010;Saccone et al, 2011]. As blocking maternal provision of female-specific Nvtra mRNA led to a complete sex-reversal of diploid offspring, surprisingly, the mother provides feminizing in addition to masculinizing information to the zygote.…”
Section: Megisd Revisitedsupporting
confidence: 63%
“…The presence of such a feminizing loop has been demonstrated for both dipteran and hymenopteran species [Pane et al, 2002;Concha and Scott, 2009;Gempe et al, 2009;Salvemini et al, 2009;Hediger et al, 2010;Saccone et al, 2011]. Only in D. melanogaster this function has been taken over by Sxl [Siera and Cline, 2008].…”
mentioning
confidence: 99%
“…Hence, the ancestral module may have consisted of tra and possibly both effectors dsx and fru to faithfully implement the sexual programs imposed by the instructive signals. Tra also plays a crucial part in maintaining the selected fate epigenetically [Saccone et al, 2011]. It acts as a cellular memory for female development, a key feature first discovered in Ceratitis .…”
Section: Insects Employ a Conserved Module In Transducing Sex-determimentioning
confidence: 99%
“…In addition it has been found that Cctra and Cctra-2 play a novel epigenetic function in the medfly, being both required to maintain the female sexual fate established during embryogenesis (Saccone et al, 2011). Analogous epigenetic functions in Drosophila are controlled by the master ON/ OFF gene Sxl, and by its auxiliary splicing factor, fl(2)d (Granadino et al, 1990).…”
Section: Introductionmentioning
confidence: 99%